MENGEMBANGKAN EKONOMI KREATIF UNTUK MASYARAKAT YANG SEHAT, CERDAS, DAN MANUSIAWI DI DESA SIDADADI, HAURGEULIS, INDRAMAYU - Rahim, Abdur; Arrasyid, Rakhmatan Lil Alamin; Najibullah, Nabilla Al-Zahira; Sudarman, Sudarman; Mariah, Siti; Abdillah, Muhammad Mukhlis; Riyanto, Riyanto; Kadarusman, Adang; Zulfikar, Nouval Annan (LPPM Universitas Bina Bangsa, 2025)
The creative economy is a concept that is increasingly relevant in this modern era, where creativity and innovation are the main keys in creating added value. The development of the creative economy in Sidadadi will not only create jobs, but can also build a healthy, intelligent and humane society. The aim of this Community Service (PkM) activity is to develop a creative economy for healthy, intelligent and humane communities in Sidadadi village, Haurgeulis, Indramayu. The results of this Community Service (PkM) activity show that the creative economy can be the main pillar in improving people's quality of life. The development of the creative economy in rural areas can increase the competitiveness and economic independence of the community. Apart from that, by utilizing digital technology, the people of Sidadadi Village can reach a wider market, not only at the local level but also nationally and internationally.